Breakfast Consumption Is Associated with Increased HEI-2015 Component Scores and Consumption of Unprocessed Foods - Jeans, Matthew (Curr Dev Nutr, 2020)
OBJECTIVES: Studies have evaluated the benefits of breakfast consumption (BC) on overall dietary quality. However, further research is warranted to determine which components of the diet, including the amount of processed foods, attribute to those findings. This study examined the associations of BC, Health Eating Index-2015 (HEI-2015) component scores, and consumption of processed foods. METHODS: This analysis used baseline data from TX Sprouts, a large school-based gardening, nutrition, and cooking randomized control trial implemented in 16 elementary schools in Austin, TX, targeting 3rd-5th grade students. Each child completed two 24-hour dietary recalls, from which HEI-2015 scores and NOVA Food Classification System scores were calculated, classifying each food item as unprocessed, processed, or ultra-processed. Breakfast was defined as a meal consumed before 10am and accounting for ≥15% of daily energy. BC groups (BCG) included: breakfast skippers (BS; no breakfast both days), intermittent breakfast consumers (IBC; breakfast one day), and regular breakfast consumers (RBC; breakfast both days). Analysis of covariance was used to examine associations between BCG, HEI-2015 scores, and NOVA scores, controlling for age, sex, race/ethnicity, free/reduced lunch (FRL) status, daily energy, and day of the week. RESULTS: The study included 668 children (mean age 9 y; 54% female, 59% Hispanic, 67% FRL) with a BCG composition of 17% BS, 37% IBC, and 46% RBC. RBC had higher total HEI scores compared to both IBC and BS (P = 0.03 and P = 0.02). Specifically, RBC compared to IBC and BS had higher total fruit (P < 0.001 and P < 0.001) and dairy (P < 0.04 and P < 0.001) intake and lower saturated fat intake (P < 0.02 and P < 0.04). RBC consumed a higher percentage of unprocessed foods than IBC and BS (P < 0.02 and P < 0.04). CONCLUSIONS: Regular BC was associated with higher dietary quality and intake of unprocessed foods; however, studies examining interventional effects of regular BC on processed food intake and diet quality are needed. FUNDING SOURCES: Supported by the National Heart, Lung, and Blood Institute.